Enhancing Farm Dams Increases Tadpole Abundance - Michelle Littlefair; Ben C. Scheele; David Lindenmayer; Maldwyn J. Evans (Ecology and Evolution)
ABSTRACT Understanding how agricultural and land management practices affect amphibian biodiversity is essential for conservation efforts in farmland. We investigated the impact of farm dam enhancement on tadpole abundance and growth in a highly modified farming landscape in south‐eastern Australia. We completed detailed surveys on 52 farm dams (artificial ponds or agricultural reservoirs). These dams were categorized into two groups: enhanced (n = 28), which had undergone management activities such as fencing to prevent livestock access and facilitate revegetation, and control (n = 24), which had not received any intervention and were subject to standard management practices similar to adjacent paddocks. Our findings revealed a notable increase in tadpole abundance across all species in enhanced dams, with 92% of all observed tadpoles recorded in these dams. Factors such as higher dissolved oxygen and greater riparian vegetation cover were positively associated with tadpole abundance, while high pH levels showed a negative association. We found no evidence that tadpole growth was influenced by dam enhancement. Concerningly, when the invasive fish Gambusia holbrooki was present, tadpoles were smaller and at earlier developmental stages. Our findings highlight the potential benefits of strategic farm dam management for improving tadpole presence in agricultural landscapes.